2022
DOI: 10.1039/d2tb01384c
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive block copolymer brush for temperature-modulated hepatocyte separation

Abstract: Hepatic tissue engineering may be an effective approach for the treatment of liver disease; however, its practical application requires hepatic cell separation technologies that do not involve cell surface modification...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…By reducing the temperature to 20 °C, adhered HUVECs were detached from PAAc-PN-750, whereas SMCs maintained their adherence to the brush. Previous reports have suggested that cell adhesion behavior differs between coculture and monoculture conditions, which has been attributed to the secreted extracellular matrix under coculture conditions or the reduced activity of cells after the application of cell-staining reagents [ 70 , 94 ]. However, similar cell adhesion behavior was observed in HUVECs and SMCs under both co-culture and monoculture conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By reducing the temperature to 20 °C, adhered HUVECs were detached from PAAc-PN-750, whereas SMCs maintained their adherence to the brush. Previous reports have suggested that cell adhesion behavior differs between coculture and monoculture conditions, which has been attributed to the secreted extracellular matrix under coculture conditions or the reduced activity of cells after the application of cell-staining reagents [ 70 , 94 ]. However, similar cell adhesion behavior was observed in HUVECs and SMCs under both co-culture and monoculture conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PNIPAAm exhibits extension and shrinkage below and above the transition temperature, respectively. The unique properties of PNIPAAm have been applied in various biomedical contexts, such as temperature-regulated drug and gene delivery systems [ [36] , [37] , [38] , [39] , [40] , [41] ], bioanalysis and biosensor devices [ [42] , [43] , [44] , [45] , [46] , [47] ], nano-actuators [ [48] , [49] , [50] , [51] ], bioseparation tools [ [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ], cell-separation materials [ [32] , [33] , [34] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ], cell culture substrates [ [71] , [72] , [73] , [74] , [75] , [76] , [77] ], and cell sheet therapy in diverse types of regenerative medicine [ 5 , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] ]. Temperature-controlled cell adhesion and detachment were applied to cell separation procedures using PNIPAAm-modified substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, applications of thermo-responsive block copolymers have mostly focused on biomedical fields, such as imaging and drug delivery. [88][89][90][91][92] In this review, we mainly discuss their applications in other fields in conjunction with their properties, based on the structure of thermo-responsive block copolymers and their nano-assemblies. According to the composition and polymer backbone, we will summarize the self-assembly behaviors and applications of five kinds of thermo-responsive block copolymers, i.e., thermo-responsive diblock copolymers containing a hydrophilic block and a thermo-responsive block, thermo-responsive diblock copolymers containing a hydrophobic block and a thermo-responsive block, doubly thermo-responsive diblock copolymers containing two thermo-responsive blocks, thermo-responsive triblock copolymers containing a hydrophilic block and two thermoresponsive blocks, and thermo-responsive triblock copolymers containing a hydrophobic block and two thermo-responsive blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, applications of thermo-responsive block copolymers have mostly focused on biomedical fields, such as imaging and drug delivery. 88–92 In this review, we mainly discuss their applications in other fields in conjunction with their properties, based on the structure of thermo-responsive block copolymers and their nano-assemblies. According to the composition and polymer backbone, we will summarize the self-assembly behaviors and applications of five kinds of thermo-responsive block copolymers, i.e.…”
Section: Introductionmentioning
confidence: 99%